EDUKASI KESEHATAN TENTANG MANAJEMEN KEBERSIHAN MENSTRUASI PADA REMAJA PUTRI SEBAGAI PENERAPAN PERILAKU PERSONAL HYGIENE - yulinda laska; Risma Ikha Paramitha (LPPM Universitas Awal Bros, 2022)
Adolescent girls need adequate information regarding welcoming the arrival of the first menstruation. This is so that young women do not experience fear when their first menstruation arrives. Information is needed so that young women can respond to the arrival of their first menstruation in a calm and comfortable manner. On the other hand, many women and girls experience difficulties in managing their menstrual hygiene, which has an impact on hygiene, health and well-being and thus affects progress towards achieving the Sustainable Development Goals for gender equality. Information related to Menstrual Hygiene Management is needed by young women to maintain their reproductive health. Poor knowledge affects bad behavior as well. Therefore, information on Menstrual Hygiene Management is needed by young women to improve their hygiene, health, and well-being. In an effort to increase the knowledge of young women about Menstrual Hygiene Management, community service activities in the form of health counseling were carried out online through the Zoom Cloud Meeting on July 21, 2022, which was attended by 36 young women with an age range of 14-22 years old. Community service activities went well and smoothly, marked by the high enthusiasm of the participants during the session of providing material and question and answer related to Menstrual Hygiene Management. The benefits obtained by the participants in this activity are that the participants gain increased knowledge related to Menstrual Hygiene Management which can be used to maintain their own cleanliness.